The Role of External Audit in Combating the Crime of Tax Evasion: An Analytical Study of some Statutory Auditor Reports - بولحبال, فاطمة الزهراء (Finance and Business Economies Review, 2023)
This study aimed to shed light on the role of external audit in combating the crime of tax evasion, by addressing general information about external audit and the nature of tax evasion in theory, and conducting a field study in the Office of the Governor of Accounts, accompanied by an analytical study of a group of its annual reports. The study concluded that the external auditor has an effective role in combating tax evasion through his mission within the institution and reviewing all accounting documents and records to ensure the validity, honesty and reliability of the financial statements and the financial position of the institution. The institution, which also allows him to discover violations, errors, and tax evasion. Addressing the receivables payable which the external auditor summarizes in his annual report.